Comparative Effectiveness and Safety of Standard-, Medium-, and High-Dose Daptomycin Strategies for the Treatment of Vancomycin-Resistant Enterococcal Bacteremia Among Veterans Affairs Patients - Nicholas Britt; Emily Potter; Nimish Patel; Molly E. Steed (2016)
Abstract Background. Vancomycin-resistant Enterococcus bloodstream infections (VRE-BSIs) are associated with significant mortality. Daptomycin exhibits concentration-dependent activity vs VRE in vitro, yet the clinical impact of higher-dose strategies remains unclear. Methods. We performed a national retrospective cohort study of hospitalized Veterans Affairs patients treated with standard-dose (6 mg/kg total body weight), medium-dose (8 mg/kg total body weight), or high-dose (≥10 mg/kg total body weight) daptomycin for VRE-BSI. Patient-related, microbiological, and outcomes data were abstracted from clinical databases. The primary outcome was overall survival, evaluated by Cox regression. Secondary outcomes included 30-day mortality, time to microbiological clearance, and creatine phosphokinase (CPK) elevation. Results. A total of 911 patients were included (standard dose, n = 709; medium dose, n = 142; high dose, n = 60). Compared to high-dose daptomycin, both standard-dose (hazard ratio [HR], 2.68; 95% confidence interval; [CI], 1.33–3.06; P = .002) and medium-dose (HR, 2.66; 95% CI, 1.33–3.92; P = .003) daptomycin were associated with poorer survival. After adjusting for confounders, the relationship between poorer survival and standard-dose (adjusted HR [aHR], 2.58; 95% CI, 1.27–4.88; P = .004) and medium-dose (aHR, 2.52; 95% CI, 1.27–5.00; P = .008) daptomycin persisted. Thirty-day mortality was significantly lower among high-dose daptomycin–treated patients compared with other dosing strategies (risk ratio, 0.83; 95% CI, .74–.94; P = .015). Compared with standard-dose daptomycin, both medium-dose (HR, 0.78; 95% CI, .55–.90; P = .012) and high-dose daptomycin (HR, 0.70; 95% CI, .41–.84; P = .006) were associated with significantly improved microbiological clearance. No difference in the risk of CPK elevation was observed between the treatment groups (P = .504). Conclusions. High-dose daptomycin was associated with improved survival and microbiological clearance in VRE-BSI.